Learning Microsoft PowerPoint 2010 - Vaccaro, Guy (InfiniteSkills, 2010)
"In this Microsoft PowerPoint 2010 training CD, expert trainer Guy Vaccaro takes you through the newly updated, widely known presentation program, Microsoft PowerPoint 2010. This computer based video training title starts with the basics of PowerPoint, the Ribbon, Quick Access Toolbar, starting PowerPoint, but quickly builds your knowledge in topics such as transitions, animating, adding clip art, managing your slides, even adding and editing video, and outputting your presentation to CD. Guy feeds you information in bite sized pieces, allowing you to better absorb the information being presented. By the completion of this computer training software on Microsoft PowerPoint 2010, you will be fully capable of creating incredible PowerPoint presentations that are sure to wow and amaze your boss, clients and co-workers. Full work files are included to allow you to work alongside with the author."--Resource description page.